Phylogenetic Analysis of Small Hive Beetles From Native to Introduced Populations - Bai, Wen Feng; Liu, Junfeng; Liu, Yuanzhen; Han, Wensu; Evans, Jay D.; Huang, Qiang (Frontiers in Genetics, 2022)
The small hive beetle (SHB), a social parasite of bee hive, is native to sub-Saharan African and has been spread to America, Europe and Australia. Recently, these beetles have invaded China, causing widespread colony collapses in the honey bee, Apis cerana. In this study, single nucleotide polymorphisms (SNPs) were identified in the beetle genome from its native range (Africa), an region that was invaded by SHB nearly 30 years ago (America) and more recent invasions (Asia). The beetles in the USA formed the earliest branch and show signs of two decades of gene flow and local adaptation to differentiate this population from the native ones. The beetles in China were deep branched and showed the highest fixation index (Fst) when compared to USA populations. The number of SNPs in over expressed genes were significantly higher compared with the transcriptome. Gene-expression profiles presented here distinguish the characters between adult and larvae SHB.